Hooray for Global Justice? Emerging Democracies in a Multipolar World - Julian Culp; Johannes Plagemann (German Institute of Global and Area Studies (GIGA), 2013)
Rising powers are fundamentally shifting the relations of power in the global economic and political landscape. International political theory, however, has so far failed to evaluate this nascent multipolarity. This article fills this lacuna by synthesizing empirical and normative modes of inquiry. It examines the transformation of sovereignty exercised by emerging democracies and shows that - in stark contrast to emerging democracies' foreign policy rhetoric - the softening of sovereignty has become the norm. The present paper assesses this softening of sovereignty on the basis of a democratic-internationalist conception of global justice. This conception holds that global justice demands the establishment of reasonably democratic transnational relations that enable people themselves to determine what else justice requires. Because we find that the exercise of soft sovereignty by emerging democracies contributes to the realization of reasonably democratic transnational relations, we conclude that this nascent multipolarity ought to be welcomed from the democratic-internationalist view of global justice.
Keywords: 300; rising powers; emerging democracies; multipolarity; sovereignty; global justice; global democracy; Brazil